Revitalisasi Anyaman Baion : Strategi Pemberdayaan Ekonomi Kreatif Berbasis Komunitas di Desa Pearaja - Dahlia Nopelina Siallagan; Berliana Simanjuntak; Rini T Simangunsong; Trimey Liria Hutauruk; Rina Handayani; Alkausar Saragih; Meslin Silalahi; Meliarta Saragih; Jaktri Okto Lumban Gaol; Togu Sitorus (Pusat Riset dan Inovasi Nasional, 2026)
This Community Service Program (PKM) aims to revitalize Baion weaving as a form of local cultural heritage while strengthening community-based creative economy in Pearaja Village. The main challenges faced by the artisans include low product value addition, limited design innovation and branding, restricted market access, and weak regeneration and institutional capacity. The program employed a Participatory Action Research (PAR) approach combined with Asset-Based Community Development (ABCD) through a co-creation framework between the service team and the artisan community. The implementation focused on institutional strengthening, enhancement of digital literacy and entrepreneurship, product design innovation, and digital-based marketing assistance. The results indicate a significant improvement in artisans’ capacity to produce more functional and market-oriented woven products, the establishment of digital marketing identities through social media platforms, and the growing awareness of institutional management and youth regeneration. Overall, the program demonstrates that integrating cultural preservation with community-based creative economy strategies can enhance business independence and ensure the sustainability of traditional crafts. These findings offer a practical empowerment model that can be replicated in other rural communities with similar cultural assets.